Management of Lecturer Certification in Standardizing the Lecturer Profession Within the Ministry of Religious Affairs (Study on the Directorate General of Islamic Education) - Nurul Huda; Iim Wasliman; R. Supyan Sauri; Deti Rostini (CV. Media Digital Publikasi Indonesia, 2026)
This research is motivated by the phenomenon that there are still many PTKI (Perguruan Tinggi Keagamaan Islam) lecturers who still have not had the opportunity to take part in Educator Certification for Lecturers who until 2023 have not been certified as many as 16,349 lecturers or 41.67% of the total PTKI lecturers of 39,452 lecturers and the low quota of certification participants within the Directorate General of Islamic Education. In 2023, as many as 1,724 PTKI lecturers have been successfully certified, with 69% of them coming from Private PTKI (PTKIS) and 31% from State PTKI (PTKIN) based on data from the Ministry of Religion of the Republic of Indonesia. The research generally aims to describe and analyse the management of lecturer certification in effort to standardise the lecturer profession at the Directorate General of Islamic Education which includes management functions of planning, organising, actuating, and controlling. This research is a qualitative research with descriptive approach. The data collection techniques used are documentation, observation and interviews. The theoretical basis used: 1) Management Theory by George R. Terry; 2) Human Resource Management Theory; dan 3) Undang-undang (UU) Nomor 14 Tahun 2005 tentang Guru dan Dosen with all its derivative regulations. The results of the study illustrate that the implementation of lecturer certification does not have a strong legal basis after 2015 and in budgeting it has not received much attention even though it is mandatory. In the organisation there is a potential for delaying opportunities for universities that have met the requirements to become PTPS (Perguruan Tinggi Penyelenggara Serdos); Implementation of lecturer certification in general has fulfilled the provisions of the lecturer certification guidelines both managed by the Directorate of PTKI and those carried out by the Certification Implementation Committee located at PTPS and in controlling the implementation of certification using an internal approach carried out by elements in PTPS through the Quality Assurance Organization and the Inspectorate General of the Ministry of Religious Affairs and external approaches are the responsibility of external supervisory apparatus, the Audit Board of the Republic of Indonesia.